Synthesis and Characterization of Metakaolin Acid-Based Geopolymer for Hydrogen Adsorption Study Using Fixed Bed Reactor - Nagasparan, Sivaneswaran (IRC, 2016)
Currently, there are researches on hydrogen storage by application of developed materials such as carbon nanotubes, zeolites, alloy metal and complex hydride. Geopolymer is anticipated as a prospective adsorbent due to economically and environmental friendly properties and lower expenditure compared to other developed materials and also derived from industrial waste. This paper conducted the study on hydrogen adsorption of synthesized metakaolin acid-based geopolymer by using fixed bed reactor. Different molarity of phosphoric acid (H3PO4) at 8M, 10M and 12M as the reaction accelerator are used at curing temperature of 80ºC to synthesis the geopolymers that were coined as phosphoric acid based geopolymers (PAGPs). The same parameters are also tested for different curing temperature of 150ºC. The synthesized PAGPs are then characterized for the particle size, surface profile, micromorphology, and texture properties by instrumentation.